Copolymerization of CO2 and epoxides mediated by zinc organyls. Issue 7 (18th January 2018) - Wulf, Christoph; Doering, Ulrike; Werner, Thomas
Abstract : Simple zinc organyls (R2 Zn) efficiently catalyze the copolymerization of CO2 and cyclohexene oxide. The effect of various reaction parameters has been studied. The reaction proceeds under halogen-free conditions and no co-catalyst is required. Abstract : Herein we report the copolymerization of CHO with CO2 in the presence of various zinc compounds R2 Zn (R = Et, Bu, i Pr, Cy and Ph). Several zinc organyls proved to be efficient catalysts for this reaction in the absence of water and co-catalyst. Notably, readily available Bu2 Zn reached a TON up to 269 and an initial TOF up to 91 h −1 . The effect of various parameters on the reaction outcome has been investigated. Poly(ether)carbonates with molecular weights up to 79.3 kg mol −1 and a CO2 content of up to 97% were obtained. Under standard reaction conditions (100 °C, 2.0 MPa, 16 h) the influence of commonly employed co-catalysts such as PPNCl and TBAB has been investigated in the presence of Et2 Zn (0.5 mol%). The reaction of other epoxides ( e.g. propylene and styrene oxide) under these conditions led to no significant conversion or to the formation of the respective cyclic carbonate as the main product.